Penggunaan Sentaku No Setsuzokushi Aruiwa Dan Soretomo Dalam Novel Norwei No Mori Karya Haruki Murakami - Tri Pradnyani, Luh Komang; Gorethy Nie Nie, Maria; Indra Pradhana, Ngurah (Humanis, 2016)
This research entitled, The Usage of Sentaku no Setsuzokushi {aruiwa} and {soretomo} on the Norwei no Mori’s Novel by Haruki Murakami. This research was focus to the explanation structure and meaning of sentaku no setsuzokushi {aruiwa} and {soretomo} on the sentences of Norwei no Mori’s Novel by Haruki Murakami, volume 5-6. On this research the author used of theory that refers to the opinion of Makino and Tsutsui (1994), and Pateda (2001). The data collection has been done by corrected reading methody and then analyzed by distribute method. The result of analyze are presented by informal method. The result of this research represented that sentaku no setsuzokushi aruiwa and soretomo can be combined with clause 1 and clause 2, word 1 and word 2, verba (ichidan doushi, godan doushi, henkaku doushi) and noun when established a sentence. Sentaku no setsuzokushi {aruiwa} had a meaning that expressed of possibility, presumption, hesitation, uncertainty, and the changes of situation. Sentaku no setsuzokushi {soretomo} are often added with [ka] word so that, had a meaning that expressed of selection.